2017
DOI: 10.2528/pierm16122502
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Angle of Attack on the Transmission of Terahertz Waves in Reentry Plasma Sheaths

Abstract: Abstract-The communication 'blackout' in the reentry stage of a space mission is a serious threat to the reentry vehicle. The terahertz (THz) technology is supposed to be a potential solution to the 'blackout' problem in the recent decade. In the present paper, the relation between the THz waves' transmission in the reentry plasma sheath and the angle of attack (AOA) of the vehicle is investigated. A three-dimensional numerical model is introduced in order to obtain the plasma parameters in the reentry plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, the model is reliable since the simulation results agree well with the RAM experiments results. This study uses the plasma sheath model to explore the antenna performance with different vehicle shapes, which is original and different from our previous works [8,12,13,16].…”
Section: The Plasma Sheaths Corresponding To Blunt-coned Vehicle and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the model is reliable since the simulation results agree well with the RAM experiments results. This study uses the plasma sheath model to explore the antenna performance with different vehicle shapes, which is original and different from our previous works [8,12,13,16].…”
Section: The Plasma Sheaths Corresponding To Blunt-coned Vehicle and ...mentioning
confidence: 99%
“…Electron density and the electron collision frequency have been revealed as the two most important plasma parameters that significantly affect antenna performance [9][10][11]. On the other hand, some previous studies reveal that the parameters of the plasma sheaths depend on many factors, e.g., atmospheric conditions [12], flight speed [8], angle of attack [13], and the shape of the vehicle [14], in which case antenna performance is affected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the hypersonic plasma sheath is influenced by many factors including the aerodynamic shape [10], the angle of attack [11,12] and the flight trajectory [13]. Besides those parameters, the plasma sheath is obviously influenced by the atmospheric conditions around the hypersonic vehicle.…”
Section: Introductionmentioning
confidence: 99%